PENINGKATAN KUALITAS INDUSTRI KONVEKSI: PENDAMPINGAN IMPLEMENTASI SAK EMKM DAN LITERASI KEUANGAN UMKM MARBLE STUDIO - Lila Widya Rahajeng; Tasnim Nikmatullah Realita; Rizalnur Firdaus (FIP UNIRA MALANG, 2026)
The aim of Improving the quality of the Garment/Convection Industry Marble Studio to improve the comprehension and proficiency of Micro, Small, and Medium Enterprises (MSMEs) in the preparation of financial statements in accordance with the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM). The program was established in response to the inadequate accounting literacy and rudimentary bookkeeping methods frequently employed by MSME owners, which often do not accurately represent their enterprises' financial status. The implementation strategy comprises multiple stages: observation, socializing, technical training, and intensive mentorship via a participatory approach. The findings indicate a notable enhancement in participants' comprehension of fundamental accounting principles, categorization of financial transactions, and compilation of financial statements in compliance with SAK EMKM. Moreover, partner MSMEs have commenced the implementation of a more organized and standardized bookkeeping system. This program aims to enhance company accountability and facilitate MSMEs' access to formal financial institutions in the future.